Assessment of mother’s awareness regarding indoor asthma triggers - Alfaituri, Asma H.; Gadalla, Salah A.; Alkhader, Anas A.; Shembesh, Aya R.; Elshekhi, Haneen M.; Elmothabal, Sanad F. (Libyan Journal of Science &Technology, 2022)
An indoor air pollutant is a very real and dangerous thing because is far more than outdoor air. A pollutant is any harmful contaminant in the air; therefore, indoor air pollution is when pollutant from substance contaminate the air indoors, such as gas, particles, rectifiers, disinfectants, tobacco smoke, spices, perfumes, and fungi that are inside the house. The objective of this study is to assess mothers' knowledge about indoor asthma triggers and their impacts on children's health. The researcher prepared a questionnaire for mothers and distributed it to children in schools for interviews. The study used children and their mothers, asthma triggers and mothers' knowledge. The cross-sectional study started in January to June 2017 descriptive design was used: population of the study included all students at Othman Ben Afan elementary school in Benghazi city. 42% of mothers do not use incense every day. Most of the mothers who answered the questionnaire read precautions posted on the label of detergent before using and 25% of mothers whose children with allergic asthma. Most of the mothers use ventilation as a control measure. The results showed a high percentage of mothers have knowledge about indoor pollutants. Besides, moderate percentages of mothers have been spraying pesticides indoors